A Causal Relationship Analysis of Factors Affecting Organizational Commitment of Employees in Headquarter of Royal Irrigation Department. - พิพัฒนวัฒนากุล, ณัฐพงศ์; Hasoontree, Natnicha (CRRU Law, Political Science and Social Science Journal, 2021)
The objectives of this study ware 1) to analyze the pathway of causal relationship influencing organizational engagement of the Central Irrigation Department personnel 2) to examine the causal relationship hypothesis, factors affecting the organizational engagement of the Royal Irrigation Department personnel. The central sample group was 360 Central Irrigation Department personnel. The researcher obtained 36 variables of causal influences on organizational engagement of the Central Irrigation Department personnel based questionnaire. The sample size was 10 times of the tool variables used. The statistics used in data analysis were frequency, percentage, average standard deviation and path analysis using AMOS program The results showed that 1) the concept framework of causal relationship patterns contributed to the organization of personnel. There are two direct influential variables: the nature of the work and the quality of life of work, and variables that have a direct and indirect influence on the organization of personnel. The Department of Central Irrigation 7 variables are safe environment and promote health. 2) The hypothesis is consistent with empirical data based on CMIN/df value of .836, p-value equal to .505 GFI equal to .9. 44 AGFI equals .934 RMR equals .001 RMSEA equals .003 NFI equals .969 TLI equals .926, and CFI equals .959. The most central irrigation department is the nature of the work, second to the quality of life of the work. All elements are described. Variance of engagement with the organization of personnel 88.30%.